MANAJEMEN PENGELOLAAN KELAS DI KELOMPOK A TK BINTANG KECIL SUKOHARJO KECAMATAN MARGOREJO KABUPATEN PATI - Sumiyati Sumiyati; Sutri Wijayanti (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2020)
ABSTRACT This research is motivated by the magnitude of the influence of the condition of the room or classroom to obtain good quality of learning. This study aims to determine the classroom management, supporting and inhibiting factors at kindergarten. This type of research is descriptive qualitative research. The research instrument is the human instrument (the researchers themselves). Data collection methods used are interviews, observation, and documentation. To analyze the research data, descriptive methods are used. The results showed that the management of class management in Group A TK Bintang Kecil Sukoharjo Margorejo Pati Regency consisted of planning, organizing, implementing, and monitoring. The plan includes the preparation of Prota, Prosem, RPPM, RPPH, and preparation for class administration. Organizing is carried out by the principal, namely the principal distributing tasks to the teacher by giving direction, then giving authority or responsibility to all teachers to manage the class well so that learning objectives are maximally achieved. While the class teacher is tasked with organizing each class which includes the setting of learning media and the selection of learning methods. The implementation includes two things, namely: first, the management of classrooms which includes seating arrangements, arrangement of teaching equipment, arrangement of class beauty and cleanliness, and ventilation and lighting. Second, is the arrangement of students. Stage of supervision, the principal always supervises the performance of teachers directly in teaching and learning activities in all classes once a week, namely on Wednesday.The supporting factors are (1) Teachers have a high spirit of solidarity and supportive knowledge, (2) adequate facilities and infrastructure, (3) Cooperation between parents and schools is well established. While the inhibiting factor is coordination that has not gone well.Keywords: Management, Classroom Management, Kindergarten.